IMPLEMENTASI MODEL BADALAS UNTUK MENINGKATKAN AKTIVITAS, KETERAMPILAN BERPIKIR KRITIS, DAN HASIL BELAJAR PADA SISWA SEKOLAH DASAR - Putera Kamarul Hidayat; Aslamiah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the activities of teachers and students, as well as to analyze students’ critical thinking skills and learning outcomes in the Indonesian language subject using the BADALAS model. The research employed a classroom action research design with both qualitative and quantitative approaches. The results indicate an improvement in activities, skills, and learning outcomes after implementing the BADALAS model. Teacher activity increased from 65%, 78%, 84%, to 100%. Student activity improved from 33%, 67%, 75%, to 100%, categorized as very active. Critical thinking skills increased from 33%, 42%, 50%, to 92%, categorized as skilled. Student learning outcomes increased from 25%, 58%, 75%, to 100%, categorized as complete.